Uniunea Europeană: o şansă şi pentru industria lemnului în România? [European Union, a chance for the Romanian wood industry?] - Teușan S; Teușan A (Bucovina Forestieră, 2005)
The present state of the wood processing industry from Germany is presented, as a possible marker for the Romanian situation. In paper are reviewed some initiatives rela-ted to the wood industry - the Wood Charta - a German governmental one, the Cluster Model - an experience from Nordrhein-Westfalen and the Stendhal project - from the Sachsen-Anhalt land. Also, the Forest Stewardship Council (FSC) and Pan-European Forest Council (PEFC) is presented too. Some modern economical orientations - including the Friendman`s - and opinions regarding the German forest policy, with its strong and weak points could serve as experience for the Romanian forestry